Evaluation of Digital Advertising Innovation and Sustainable Economic Policies on Consumer Trust: A Case Study of Avoskin in Medan: Evaluasi Inovasi Iklan Digital dan Kebijakan Ekonomi Berkelanjutan terhadap Kepercayaan Konsumen: Studi Kasus Produk Avoskin di Kota Medan - Tiara Tessalonica Dewinta Silitonga; Hommy Dorthy Ellyanty Sinaga (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
This research aims to analyze the influence of digital advertising innovation and sustainable economic policies on consumer trust in Avoskin products, focusing on college students in Medan. This study uses a quantitative approach with a survey method, using purposive sampling to select respondents who are college students in Medan and have used or are currently using Avoskin products. A total of 100 valid respondents were obtained through the distribution of a Likert scale-based questionnaire, and then the data were analyzed using multiple linear regression. The results show that digital advertising innovation has a positive and significant effect on consumer trust, confirming that creative and interactive advertising strategies can enhance brand credibility. Sustainable economic policies were also proved to have a positive and significant effect, as consumers increasingly value ethical and environmentally friendly business practices. Simultaneously, both variables significantly influence consumer trust. These findings highlight the importance of combining innovative digital marketing strategies with a commitment to sustainability to strengthen the brand-consumer relationship. For local brands like Avoskin, the transparent implementation of sustainable practices supported by digital innovation, not only improves competitiveness but also builds long-term trust, especially among the younger generation.